Auger decay rates of core hole states using equation of motion coupled cluster method - Ghosh, Aryya; Vaval, Nayana; Pal, Sourav (Chemical Physics, 2017)
The recent development of Linac coherent light source high intense X-ray laser makes it possible to create double core ionization in the molecule. The generation of double core hole state and its decay is identified by Auger spectroscopy. The decay of this double core hole (DCH) states can be used as a powerful spectroscopic tool in chemical analysis. In the present work, we have implemented a promising approach, known as CAP-EOMCC method, which is a combination of complex absorbing potential (CAP) and equation -of-motion coupled cluster (EOMCC) approach to calculate the lifetime of single and double core hole states. We have applied this method to calculate the lifetime of the single core hole (K-LL) and double core hole (KK-KLL) states of CH4, NH3 and HF molecules. The predicted lifetime is found to be extremely short. (C) 2016 Elsevier B.V. All rights reserved.